The Sustainable Development Practices Role and Transformational Leadership: Interaction and Impact on the Financial Performance - Jundi, Khaled; Ghazalat, Anas; Yahya, Sofri (Journal of Reviews on Global Economics, 2019)
The purpose of this study is to explore the direct relationship between sustainable development practices and financial performance. It also examines the moderating effect of transformational leadership approach on this relationship. Using primary data sources, this study presents a case study of the Jordanian construction industry. A survey of 290 managing directors or his appointed representative for 1113 construction companies in Jordan. Data were collected from October 2017 until April 2018. The multiple regression analysis and hierarchical multiple regression analysis are used to verify the hypotheses of this study. Analyzed data reveals a positive relationship among sustainability development factors (i.e. environmental, economic, social aspects) and financial performance. Furthermore, the result of hierarchical multiple regression has shown that the moderating effect of transformational leadership is significant only on the relationship between Environmental aspects and financial performance. Also, the transformational leadership does not moderate the impact of â€œEconomic aspects and Social aspectsâ€ on the financial performance. This work strengthens the previous findings in the available literature as to how sustainability practices enhance the construction firms’ performance. Moreover, this study involves the moderating role of transformational leadership on the main relation which also proves and supports the existing knowledge on performance measurement and performance of organisations. This study also contributes to practical aspects, by providing contractors with insights into implementing sustainability practices and tools to measure the sustainable construction firms’ performance.